PERANCANGAN WEBSITE E-COMMERCE PRODUK MARKISA MANIS MENGGUNAKAN STRUKTUR NAVIGASI DAN UML - -, Suharni; Ratnasari, Lilis; Lestari, Muji; Haikal, Farid (JURNAL REKAYASA INFORMASI, 2024)
Sweet Markisa is an MSME activity (Micro small and Medium Enterprises) with the resulting product being pure passion fruit essence. Websites as information media are very useful in helping MSME activities. It is hoped that the E-Commerce application that will be designed will make things easier and helpful for MSMEs of Sweet Markisa in conveying information about the products being sold, process transactions and expand marketing reach so as to increase sales.The stages in making the application using the waterfall model.The application to be created must be easy to communicate with system designers and programmers related to the needs of application users. The design Model use a Navigation Structure, UML and I/O interface. Diagrams from the UML are Usecase, activity, and class diagrams. The results of the system design created can be used as a reference for implementation by system developers in creating applications which can help MSME activities.